Tenure and Forest Income: Observations from a Global Study on Forests and Poverty - Jagger, P.; Luckert, M.K.; Duchelle, Amy E.; Lund, J.F.; Sunderlin, William D. (Elsevier, 2014)
We explore the relationship between tenure and forest income in 271 villages throughout the tropics. We find that state-owned forests generate more forest income than private and community-owned forests both per household and per hectare. We explore whether forest income varies according to the extent of rule enforcement, and congruence (i.e., overlap of user rights between owners and users). We find negative associations between enforcement and smallholder forest income for state-owned and community forests, and positive associations for privately owned forests. Where user rights are limited to formal owners we find negative associations for state-owned forests. Overlapping user rights are positively associated with forest income for community forests. Our findings suggest that policy reforms emphasizing enforcement and reducing overlapping claims to forest resources should consider possible negative implications for smallholder forest income.